Cara baru mendidik anak sejak dalam kandungan F. Rene Van De Carr, Marc Lehrer ; penerjemah, Alwiyah Abdurrahman ; penyunting Ary Nilandari - CARR, F. Pene Van De; Lehrer, Marc; Abdurrahman, Alwiyah; Nilandari, Ary (2003)
184 hlm ilus 23 cm